Mapping Alterations Induced by Long-Term Axenic Cultivation of Leishmania amazonensis Promastigotes With a Multiplatform Metabolomic Fingerprint Approach - Crepaldi, Frederico; de Toledo, Juliano Simões; do Carmo, Anderson Oliveira; Ferreira Marques Machado, Leopoldo; de Brito, Daniela Diniz Viana; Serufo, Angela Vieira; Almeida, Ana Paula Martins; de Oliveira, Leandro Gonzaga; Ricotta, Tiago Queiroga Nery; Moreira, Douglas de Souza; Murta, Silvane Maria Fonseca; Diniz, Ariane Barros; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Leishmaniases are widespread neglected diseases with an incidence of 1.6 million new cases and 40 thousand deaths per year. Leishmania parasites may show distinct, species-specific patterns of virulence that lead to different clinical manifestations. It is well known that successive in vitro passages (SIVP) lead to the attenuation of virulence, but neither the metabolism nor the pathways involved in these processes are well understood. Herein, promastigotes of a virulent L. amazonensis strain recently isolated from mice was compared to SIVP derived and attenuated promastigotes, submitted to 10, 40 and 60 axenic passages and named R10, R40 and R60, respectively. In vitro assays and in vivo tests were performed to characterize and confirmed the attenuation profiles. A metabolomic fingerprint comparison of R0, R10 and R60 was performed by means of capillary electrophoresis, liquid and gas chromatography coupled to mass spectrometry. To validate the metabolomic data, qPCR for selected loci, flow cytometry to measure aPS exposure, sensitivity to antimony tartrate and ROS production assays were conducted. The 65 identified metabolites were clustered in biochemical categories and mapped in 8 metabolic pathways: ABC transporters; fatty acid biosynthesis; glycine, serine and threonine metabolism; β-alanine metabolism; glutathione metabolism; oxidative phosphorylation; glycerophospholipid metabolism and lysine degradation. The obtained metabolomic data correlated with previous proteomic findings of the SVIP parasites and the gene expression of 13 selected targets. Late SIVP cultures were more sensitive to SbIII produced more ROS and exposed less phosphatidylserine in their surface. The correspondent pathways were connected to build a biochemical map of the most significant alterations involved with the process of attenuation of L. amazonensis. Overall, the reported data pointed out to a very dynamic and continuous metabolic reprogramming process, accompanied by changes in energetic, lipid and redox metabolisms, membrane remodeling and reshaping of parasite-host cells interactions, causing impacts in chemotaxis, host inflammatory responses and infectivity at the early stages of infection.